MENELUSURI KEHENDAK TUHAN MELALUI RAJUTAN BAHASA: STRUKTUR ESTETIKA BAHASA AL-QUR’AN - Lutfi Rahmatullah (IAIN Kediri, 2015)
This paper aims to explore the significance of ‘language’ in shaping human civilization; even God chose ‘language’ as a medium of communication with His people. It is undeniable that ‘Arabic’ language is the language of theal-Qur’an. Departing from this, this paper will study the aesthetic structures of the Qur’anic language because the language contains divine, absolute dimension of culture and humanity. Using a philosophical approach, this paper will describe the significance of human language existance, while the structure of the aesthetic language of the al-Qur’an.Keywords: Bahasa, Struktur al-Qur’an, Estetika